cGAS in nucleus: The link between immune response and DNA damage repair - Song, Jia-Xian; Villagomes, Deana; Zhao, Hongchang; Zhu, Min (Frontiers in Immunology, 2022)
As the first barrier of host defense, innate immunity sets up the parclose to keep out external microbial or virus attacks. Depending on the type of pathogens, several cytoplasm pattern reorganization receptors (PPRs) exist to sense the attacks either from foreign or host origins, following trigger of the immune response to battle with the infections. Among them, cGAS -STING is the major pathway that mainly responds to microbial DNA, DNA virus infections, or to self-DNA, which mainly comes from genome instability by-product or released DNA from the mitochondria. cGAS was initially found functional in the cytoplasm, while intriguing evidence indicates that cGAS exists in the nucleus where it is involved in the DNA damage repair process. Since the close connection between DNA damage response with immune response and cGAS recognize DNA in length-dependent but DNA sequence-independent manners, it's urgent to clear the function balance of cGAS in the nucleus versus cytoplasm and how it is shieled from recognizing the host origin DNA. Here we outline the current conception of immune response and the regulation mechanism of cGAS in the nucleus. Furthermore, we will shed light on the potential mechanisms that are restricted to take away from self-DNA recognition, especially how post-translational modification regulates cGAS functions.